Circulating long noncoding RNA GAS5 is a novel biomarker for the diagnosis of nonsmall cell lung cancer - Liang, Wenjun; Lv, Tangfeng; Shi, Xuefei; Liu, Hongbing; Zhu, Qingqing; Zeng, Junli; Yang, Wen; Yin, Jie; Song, Yong (Medicine (Baltimore), 2016)
The recently discovered long noncoding RNAs have the potential to regulate many biological processes, which are aberrantly expressed in many tumor types. Our previous study showed that the long noncoding RNA-growth arrest-specific transcript 5 (GAS5) was decreased in lung cancer tissue, which contributed to the proliferation and apoptosis of nonsmall cell lung cancer (NSCLC). GAS5 was also associated with the prognosis of lung cancer patients. These results suggest that GAS5 may represent a novel prognostic indicator and a target for gene therapy in NSCLC. However, the expression and diagnosis significance of GAS5 in the plasma of NSCLC patients was unknown. The plasma samples were more readily available than the tissue samples in clinical, so we designed the study to investigate the diagnosis value of GAS5 in blood samples. In our study, 90 patients with NSCLC and 33 healthy controls were included. Blood samples were collected before surgery and therapy. We extracted the free RNA in the plasma and analyzed the expression of GAS5 with quantitative reverse transcription PCR. Suitable statistics methods were used to compare the plasma GAS5 levels of preoperative and postoperative plasma samples between the NSCLC patients and healthy controls. Receiver-operating characteristic curve analysis was used to evaluate the diagnostic sensitivity and specificity of plasma GAS5 in NSCLC. The results showed that GAS5 was detectable and stable in the plasma of NSCLC patients. Furthermore, the plasma levels of GAS5 were significantly down-regulated in NSCLC patients compared with healthy controls (P = 0.000). Moreover, GAS5 levels increased markedly on the seventh day after surgery compared with preoperative GAS5 levels in NSCLC patients (P = 0.003). GAS5 expression levels could be used to distinguish NSCLC patients from control patients with an area under the curve of 0.832 (P < 0.0001; sensitivity, 82.2%; specificity, 72.7%). The combination of the GAS5 and carcinoembryonic antigen could produce an area of 0.909 under the receiver-operating characteristic curve in distinguishing NSCLC patients from control subjects (95% confidence interval 0.857-0.962, P = 0.000). We have demonstrated that GAS5 expression was decreased in NSCLC Plasma. Plasma samples were more accessible than tissue samples in clinical; therefore, GAS5 could be an ideal biomarker for the diagnosis of NSCLC.